Process Skills Mathematics Learning in Elementary School - Yantoro, Yantoro; Kurniawan, Dwi Agus; Perdana, Rahmat; Rivani, Putri Ayu (Jurnal Pendidikan dan Pengajaran, 2021)
There are still many students who have difficulty learning mathematics. It is because mathematics contains symbols, calculations and abstract concepts that students find it difficult to understand mathematical material. In addition, the process skills of students at the elementary school level are deficient. This study aimed to analyze the differences and the relationship between students' process skills between elementary school students in mathematics with speed and discharge material. This study uses quantitative methods with associative and comparative types. The population in this study amounted to 216 students. The research sample amounted to 72 using the simple random sampling technique. The methods used to collect data are observation, questionnaires, and tests. The instruments used to collect data are questionnaires and test questions. The techniques used to analyze the data are qualitative descriptive analysis, quantitative, and inferential statistics. The study results were that there were significant differences in student process skills between elementary school (SD) and MIS (Masrasah Ibtidaiyah) students in learning mathematics with speed and discharge material. From the correlation test results, it is known that there is a relationship between the variable process skills of elementary school students and Madrasah Ibtidaiyah in mathematics with speed and discharge. Public schools have the same portion for all subjects, while madrasah Ibtidaiyah has a more significant portion for religious subjects.